Sixth Five Year Plan 1980-85 A Summary - Planning Commission (Planning Commission, 1980)
Over the past 30 years of planned economic development considerable progress has been made in the economy towards the basic objectives of growth, modernisation, self-reliance and social justice; there has also been a diversification of the economic structure, these achievements constitute a positive national asset for launching a more direct attack on poverty and underdevelopment in tire Sixth Plan, the task is enormous and made all the more difficult by the sharp deterioration in the external environment. The Sixth Five-Year Plan has been formulated taking into account the achievements and shortcomings of the past three decades of planning, recent economic developments which nave a bearing on the growth prospects of the economy in the medium term as well as the vision of the future as reflected in the long term perspective
Government of India Planning Commission